The Influence of Complaint Handling, Marketing Communication and Trust on Loyalty (Marketing Management Literature Review) - Agustin Hermawati (Dinasti International Journal of Management Science, 2022)
Literature Article Review of the Effect of Complaint Handling, Marketing Communication and Trust on Customer Loyalty PT Bank BCA KCU Semarang is a scientific article that aims to build a research hypothesis of influence between variables that will be used in future research, within the scope of Marketing Management science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. Research data is primary data collected through questionnaires in the form of google forms, as well as secondary data collected with documentation techniques. Sampling with random samples, while the calculation technique uses the Slovin formula so that a sample of 400 is obtained. But only 150 respondents were willing to fill out the questionnaire. Data analysis techniques use multiple regression analysis. The results of this Literature Review article are: 1) Complaint Handling affects Loyalty; 2) Marketing Communications affect Customer Loyalty; 3) Trust affects Customer Loyalty; Customers.